Advances in understanding multifunctionality of Barley stripe mosaic virus γb protein. - Zhihao Jiang; Meng Yang; Dawei Li (PLoS Pathogens)
Plant viruses usually encode versatile but limited number of proteins to reshape the cellular microenvironment, suppress or co-opt host pathways and proteins for their own benefit. Barley stripe mosaic virus (BSMV, Hordeivirus hordei) is a positive single-stranded RNA virus that infects both monocots and dicots. Among its seven encoded proteins, the γb protein exhibits remarkable multifunctionality despite being the smallest one. By interacting with various viral and host proteins, γb acts as a master regulator participating in almost all steps of the viral life cycle, including replication, movement, virion morphogenesis and vertical transmission, in addition to counteracting several layers of host defenses. In this review, we systematically summarize current understanding of the γb protein multifunctionality and discuss its implications in the ongoing co-evolutionary battle between host plants and invading viruses.